Sistem Informasi Status Gizi Balita pada Posyandu Kelurahan Amplas Menggunakan Metode K-Nearest Neighbor - Feby Ariska; Triase Triase; Adnan Buyung Nasution (Pusat Riset dan Inovasi Nasional, 2026)
Posyandu (Integrated Health Post) is a public health facility that plays a crucial role in monitoring the development of toddlers. The process of recording nutritional status at te Amplas Village Posyandu is still handwritten in notebooks, requiring a long time to collect and analyze data from all toddlers, and parents often lose or forget their Posyandu cards. This study aims to develop an information system that can assist Posyandu cadres in automatically classifying toddler nutritional status. The K-Nearest Neighbor (KNN) method was used, with variables such as age, weight, height, mid-upper arm circumference, and gender. The training data used in this study used WHO standards as a reference for nutritional status. The system was tested using the K-value to achieve the best accuracy. The test results showed that the KNN method was able to classify toddler nutritional status with excellent accuracy. The developed information system also provides data recording features and toddler development graphs. This system makes monitoring toddler nutritional status faster, more accurate, and easier for Posyandu (Integrated Health Post) cadres.